Iron and Harmful Algae Blooms: Potential Algal-Bacterial Mutualism Between Lingulodinium polyedrum and Marinobacter algicola - Yarimizu, Kyoko; Cruz-López, Ricardo; Carrano, Carl J. (Frontiers in Marine Science, 2018)
Phytoplankton blooms can cause acute effects on marine ecosystems either due to their production of endogenous toxins or due to their enormous biomass leading to major impacts on local economies and public health. Despite years of effort, the causes of harmful algal blooms (HAB) are still not fully understood. Our hypothesis is that bacteria that produce photoactive siderophores may provide a bioavailable form of iron to commensally associated phytoplankton, which could in turn affect algal growth and bloom dynamics. Here we report a laboratory-based study of binary cultures of the dinoflagellate Lingulodinium polyedrum, a major HAB species, with Marinobacter algicola DG893, a phytoplankton-associated bacterium that produces the photoactive siderophore vibrioferrin. Comparing binary cultures of L. polyedrum with both the wild type and the vibrioferrin minus mutant of M. algicola shows that bacteria are necessary to promote dinoflagellate growth and that this growth promotion effect is at least partially related to the ability of the bacterium to supply bioavailable iron via the siderophore vibrioferrin. These results support the notion of a carbon for iron mutualism in some bacterial-algal interactions.